PENGGUNAAN LIMBAH KULIT SAMAK KROM PADA KEMASAN PRODUK OLAHAN KAYU GAHARU - Agung Wicaksono; Retno Purwandari (Institut Seni Indonesia Yogyakarta, 2020)
This research needs to be carried out to help improve the people’s economy. Stems from seeing the availability of chromium leather waste in Magetan that is not utilized properly. O n the other hand, there is a quality product that is processed products of agarwood in West Kalimantan, especially in the CV Global Agarwood Station but not selling because the packaging is not designed to be attractive. Agarwood can be processed into chips, oils that can be used for aromatherapy and parfume, and agarwood sculpture. Therefore, this research is expected to be able to realize the packaging of agarwood processed wood products by considering the composition of the design elements of the chrome tanned leather waste material in Magetan. This research method uses the flow or stages, namely predesign, design, embodiment, and presentation. Chrome leather packaging products produced apply the composition of design elements from two cultures in West Kalimantan, namely Dayak and Malay with hand sewing techniques, machine sewing, laser, and punching. Cultural elements of both, such as flora, specificity of the ornaments, and the specificity of colors appearing on the product packaging. This product packaging is expected to increase the selling value of agarwood processed wood products.Penelitian ini perlu dilaksanakan untuk membantu peningkatan perekonomian rakyat. Bermula dari melihat ketersediaan limbah kulit samak krom di Magetan yang tidak dimanfaatkan dengan baik. Di lain hal, ada suatu produk berkualitas yakni produk olahan kayu gaharu yang ada di Kalimantan Barat khususnya di CV Global Agarwood Station tetapi kurang menjual karena kemasannya tidak dirancang menarik. Kayu gaharu dapat diolah menjadi serpihan kayu (chip), minyak yang bisa dimanfaatkan untuk aromaterapi dan parfum, serta agarwood sculpture. Untuk itu, melalui penelitian ini diharapkan mampu mewujudkan kemasan produk olahan kayu gaharu dengan mempertimbangkan komposisi elemen desain dari bahan limbah kulit samak krom yang ada di Magetan. Metode penelitian ini menggunakan alur atau tahapan, yakni: praperancangan, perancangan, perwujudan, dan penyajian. Produk kemasan berbahan kulit samak krom yang dihasilkan mengaplikasikan komposisi elemen desain dari dua budaya yang ada di Kalimantan Barat, yaitu Dayak dan Melayu dengan teknik jahit tangan, jahit mesin, laser, dan punching. Unsur-unsur budaya dari keduanya, seperti flora, kekhasan ornamen, dan kekhasan warna dimunculkan pada kemasan produknya. Dengan kemasan produk ini diharapkan menambah nilai jual produk olahan kayu gaharu.